Placer gold occurrences along the major rivers of Nepal Himalaya and their possible primary sources - Kaphle, K. P.; Joshi, P. R.; Khan, H. R. (Journal of Nepal Geological Society, 1996)
Recent exploration in Lungri Khola area, Rolpa district, midwestern Nepal helped to delineate a discontinuous 1.5 to 40 m thick and about 30 km long primary gold mineralization zone in the Precambrian greenschists and Lower Paleozoic micaceous marbles of the Lesser Himalaya. The gold content in these lodes vary from 0.01 to 6.7 ppm. In eastern Nepal occurrences of primary gold is recorded in quartz-biotiteschist, amphibolite and pegmatite bodies in Sunmai and Bering Khola of Ilam district. Fine flakes of gold also occur in the pyritiferous quartz beds/lenses in chlorite-sericite phyllite and quartzite of Bamangaon polymetallic prospect, Dadeldhura district, far western Nepal. In this prospect the gold content is from 0.2 to 0.8 ppm, and one sample showed up to 14 ppm. Primary gold occurrences are also detected in few irregular quartz-pyrite veins and iron-copper sulphide bearing quartzite lying close to the amphibolite bodies. Some pyrite bearing radioactive quartzite beds in Banku Quartzite of Purchauni Crystalline Complex exposed at Boregad, Bangabagar, Baggoth and Jamari Gad area in Darchula and Baitadi districts, far western Nepal also contain gold. The gold content in the radioactive quartzite varies from 0.2 to 1.2 ppm and in some pyritiferous radioactive quartzite floats it reaches up to 5.06 ppm. The primary gold appears to be of synsedimentary, hydrothermal and possibly volcanogenic in origin. Placer gold is derived from primary sources and deposited at favourable locations along the river flood plains. Further investigations in similar geological terrain may help to identify economically viable primary as well as placer gold deposits in the Nepal Himalaya.